ANALYSIS OF ORGANIC MATERIAL CONTENT AND ABUNDANCE OF MACROZOOBENTHOS IN THE SOUTH BENGKALIS ISLAND, RIAU PROVINCE - Razid, Muhamad; Amin, Bintal; Efriyeldi, Efriyeldi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
ABSTRACT This study was conducted in July-August 2020 by using sediment samples and macrozoobenthos in the southern part of Bengkalis Island, Riau Province. The aim of this study is to find out how much the organic matter content, the abundance of macrozoobenthos, and the correlation between the organic matter content of the sediments to the abundance of macrozoobenthos. This study used a survey method consisting of 3 stations with 3 transects in each station. The organic matter content of sediments revolved from 4.85 to 8.52% in the waters of the southern part of Bengkalis Island. The highest organic matter content was at station III, namely 8.52%, while the lowest organic matter content was at station II namely 4.85%. The abundance of organisms found at the three research stations was 4.04 to 5.96 ind/m2. The abundance average at all macrozoobenthic research stations was 4.93 ind/m2. The results of simple linear regression analysis of organic matter content and abundance of macrozoobenthos showed a very weak correlation.